A note on Ulam stability of some fuzzy number-valued functional equations - Wu, Jian-Rong; Jin, Zhen-Yu (Fuzzy sets and systems, 2019)
This note investigates the Ulam stability of the following fuzzy number-valued functional equations in Banach spaces by using the metric defined on a fuzzy number space:f(x+y2)+f(x−y2)=f(x)andf(ax+by)=rf(x)+sf(y).